The Influence of Brand Equity on Consumer's Purchase Decision: A Quantitative study - Muhammad Ilham Wardhana Haeruddin (PINISI Discretion Review, 2021)
This study aims to explain influence between the elements of brand equity (Brand Awareness and Brand Loyalty) on Purchasing Decisions. The population in this study were consumers of PT. Semen Tonasa in Pangkep Regency. While the number of samples is as many as 63 respondents who were selected based on purposive sampling technique for two months of research at the Labakkang Jaya Shop. The data collection method used was the distribution of questionnaires that had been tested for validity and reliability. Multiple regression is used to analyize the data. From the regression analysis, the equation Y = 4.695 + 0.425X1 + 0.458X2 is obtained. The results of this study indicate that Brand Awareness and Brand Loyalty simultaneously have a positive and significant effect on the purchase decision (Y) of Semen Tonasa. The variable of the brand equity element that has the dominant effect on the purchasing decision of Semen Tonasa is Brand Loyalty with a regression coefficient value of 0.458.